Performing Minority Identity: Storytelling Practices Of Indonesian Migrant Caregivers On Tiktok - Jihan Farida Putri; Maylanny Christin (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to analyze how Indonesian migrant caregivers in Japan construct and perform their minority identities through storytelling practices on TikTok. It also explores the extent to which these representations open up opportunities for the emergence of micro-celebrities in the digital space. Previous studies have tended to position migrant workers as objects of structural analysis, thus remaining limited in explaining how they actively encode, negotiate, and represent their lived experiences through self-produced narratives on social media. To address this gap, this study employs a qualitative approach using Qualitative Content Analysis (QCA) on ten TikTok videos produced by Indonesian migrant caregivers, with thematic analysis assisted by NVivo software. The findings identify seven main themes: emotional burden, occupational risks, workplace realities, self-regulation, workplace relationship dynamics, communication barriers, and personal growth. Through the lens of Stuart Hall’s theory of representation, these narratives reflect dominant, negotiated, and oppositional readings. Digital storytelling functions not only as a medium for self-expression but also as a strategic performative practice that generates authenticity capital, reinforces niche identity, and builds parasocial bonds with the audience. This study contributes to expanding communication research on performative minority identity at the intersection of digital storytelling, platform visibility, and migrant workers’ self-representation.